Pengelolaan BUM Desa Loh Jinawi Dalam Optimalisasi Potensi Desa Galengdowo Kecamatan Wonosalam Kabupaten Jombang - Isna Yunita Sari; Tukiman Tukiman (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Each village has different potentials ranging from the potential of natural resources, culture and local industry of the village. With the potential of the village, it is necessary to optimize the potential of the village so that the available resources can produce usefulness for the community. Optimizing village potential can be cultivated through BUM Desa. BUM Desa is a village business institution organized by the community and village government in order to improve the village economy and based on the needs and potential of the village. Loh Jinawi Village BUM is one of the BUM Desa in Galengdowo Village, Wonosalam District, Jombang Regency. Galengdowo village has superior potential, namely cow's milk. This study aims to determine the management of BUM Desa Loh Jinawi in optimizing the potential of the village. The research method used is qualitative. By using the concept of BUM Desa management principles according to David Wijaya, namely cooperative, participatory, emancipatory, transparent, accountable and sustainable. The result of the research is that overall BUM Desa Loh Jinawi has implemented the management principles of BUM Desa in optimizing the potential of Galengdowo Village, Wonosalam District, Jombang Regency.